Bioethics and Racism practices, conflicts, negotiations and struggles - Botrugno, Carlo; Raymundo, Marcia Mocellin 19XX-; Re, Lucia 1953- (De Gruyter, 2023)
This volume aims to explore some of the practices, conflicts, negotiations and struggles at the interplay of bioethics and racism. This requires shedding light on the hegemonic power relationships that condemn some population groups to a condition of subjugation, suffering, and oppression. By unpacking notions that have been taken for granted and dismantling rhetorics that are veiled in discourses and rationales pertaining to race and racism, we highlight possible ways in which bioethics can operate across disciplinary boundaries and strengthen its connection with equity and social justice, which also entails striving for a "bioethics in action"